Relationship between therapeutic communication and patient satisfaction at the community health center: A cross-sectional study - Yuliana, Yuliana; Aulia, Siti; Filomena, Maria (Journal of Community Nursing and Primary Care, 2024)
Background: Therapeutic communication is a fundamental component of healthcare services, as it facilitates effective interactions between healthcare providers and patients and contributes to patient-centered care. Effective therapeutic communication is particularly important in community health centers, where patient satisfaction reflects the quality of primary healthcare services. Objective: This study aimed to examine the relationship between therapeutic communication skills and patient satisfaction at community health centers (Puskesmas). Methods: A quantitative study with a correlational design was conducted involving 200 patients receiving services at Puskesmas. Data were collected using structured questionnaires that assessed therapeutic communication skills and patient satisfaction. Statistical analysis was performed using correlation tests to determine the strength and direction of the relationship between therapeutic communication skills and patient satisfaction. Results: The findings demonstrated a significant positive relationship between therapeutic communication skills and patient satisfaction. Among the dimensions of therapeutic communication, empathy and active listening were identified as the strongest contributors to patient satisfaction. Conclusion: Therapeutic communication skills are significantly associated with patient satisfaction in community health centers. Enhancing empathy, active listening, and clarity of information delivery through structured training programs for healthcare providers is recommended to improve patient satisfaction and overall quality of primary healthcare services.